Land cover change impact analysis: an integration of remote sensing, GIS and DPSIR framework to deal with degraded land in Lepan Watershed, North Sumatra, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Rahmawaty, Rauf, A, Harahap MM, Kurniwan H. 2022. Land cover change impact analysis: an integration of remote sensing, GIS and DPSIR framework to deal with degraded land in Lepan Watershed, North Sumatra, Indonesia. Biodiversitas 23: 3000-3011. The Lepan Watershed is located in North Sumatra Province, Indonesia. The types of land cover in the Lepan Watershed were examined to analyze the impact of changes in land cover over periods of five years and ten years (2009-2014-2019). This study used three analyses: analysis of land cover type, land cover change, causes and impacts of those changes, and government responses to those changes. Analysis of land cover types and changes was conducted using geographic information system (GIS). The land cover change impacts were analyzed using the driving forces, pressure, state, impact, and response (DPSIR) approach. Twelve land cover types were identified, i.e., water body, dryland forest, industry, mixed garden, open land, mangrove, rubber plantation, oil palm plantation, settlement, paddy field, shrub, and pond. For five years, changes in land cover occurred in the Lepan Watershed. During ten years (2009-2019), the mixed garden, oil palm plantation, and settlement increased, while dryland forest, mangrove, rubber plantation, paddy field, shrub, and pond decreased. The water body and industry land cover types did not undergo extensive changes over the past five and ten years. Changes in land cover resulted in the following impacts: decreasing biodiversity, increasing the risk of floods, increasing damage to mangroves, and decreasing rice production. The prevention of land-use change to maintain environmental sustainability is a shared responsibility of all stakeholders.